Main and ancillary proceedings in the light of the EU Insolvency Regulation 1346/2000 on international insolvency law and innovative companies - Luigi Lai (International Entrepreneurship Review, 2016)
The activity of advancing research in entrepreneurship in the global context cannot disregard insolvency law. Insolvency and entrepreneurship are different sides of the same coin. For this reason the objective of this paper is to draft the main features of the EU regulation 1346/2000 on international insolvency law. The European Union attempts on insolvency situation deeply changed during the last decades. Nowadays insolvency is considered as a possible event which may occur, and it is not considered anymore as the unfortunate end of an entrepreneurship experience, consequently the EU regulated the cases when an insolvent company has creditors or assets across the European Union. The author drafts the main problematic concerning the coordination concerning international insolvency cases within the EU and shows which is the road map that the EU commission is tracing, demonstrating that entrepreneurship is too an important value not to be sufficiently protected.